2006
DOI: 10.1143/jjap.45.5274
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-Flight Secondary Mass Spectrometry Analysis of Isotope Composition for Measurement of Self-Diffusion Coefficient

Abstract: The analysis of isotope ratio in a material consisting of a single element was developed as a fundamental technique to determine a self-diffusion coefficient in a melt based on time-of-flight secondary mass spectrometry (TOF-SIMS). The selfdiffusion coefficient for a pure Ge melt was measured using the stable isotope 73 Ge as a tracer under a homogeneous static magnetic field in order to evaluate the influence of thermal convection upon isotope distribution. The results obtained showed that the magnetohydrodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The analytical capability of TIMS was not further improved, even in very recent studies (Gautier et al 2012). In rare cases, gas source mass spectrometry (Graham et al 1951;Kipphardt et al 1999) and secondary ion mass spectrometry (Nishimura et al 1988 ;Onishi et al 2006) were also employed. Graham et al (1951) reported the abundances of the Ge isotopes in germanium tetrachloride and tetrafluoride prepared from mineral samples of different geological and geographical origins.…”
Section: Early Methods To Measure Ge Isotope Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical capability of TIMS was not further improved, even in very recent studies (Gautier et al 2012). In rare cases, gas source mass spectrometry (Graham et al 1951;Kipphardt et al 1999) and secondary ion mass spectrometry (Nishimura et al 1988 ;Onishi et al 2006) were also employed. Graham et al (1951) reported the abundances of the Ge isotopes in germanium tetrachloride and tetrafluoride prepared from mineral samples of different geological and geographical origins.…”
Section: Early Methods To Measure Ge Isotope Ratiosmentioning
confidence: 99%
“…Although no natural variations were reported, this study refined the atomic weight of Ge. Secondary ion mass spectrometry was also used in several studies (Nishimura et al 1988 ;Onishi et al 2006) but not widely applied.…”
Section: Early Methods To Measure Ge Isotope Ratiosmentioning
confidence: 99%
“…Going to space, where most effects from the gravitational force can be eliminated, is expected to be the best way to solve the problem. Recently, the application of a static magnetic field to an electrically conducting melt has been recognized as a method to substitute for a low-gravity environment [10,11], because the motion of the melt is reduced by interaction between the imposed static magnetic field and the electric current induced by the field [12]. There have been several reports concerning a cold crucible induction furnace setup fitting in the bore of a magnet [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Nishimura et al 8 determined the isotopic abundance of a pellet of highly purified germanium by secondary ion mass spectrometry (SIMS). Onishi et al 9 employed time of flight secondary ion mass spectrometry (TOF-SIMS) to study the diffusion in Ge rods. Some authors have used inductively coupled plasma mass spectrometry (ICPMS) to measure geological and meteorite samples.…”
Section: Introductionmentioning
confidence: 99%